Tarbiyah in the Digital Age: An Islamic Behavioral Framework for Reducing the Duration of Gadget Use in Preschoolers - Abdillah, Husni; Pangastuti, Ratna; Erfansyah, Nasrul Fuad (Sekolah Tinggi Agama Islam Taruna Surabaya, 2025)
This study addresses the growing issue of excessive gadget use by framing behavior modification within the principles of Islamic child-rearing (Tarbiyah al-Awlad). The primary aim was to reduce gadget dependency and screaming behavior in a preschooler by applying an intervention model that is spiritually meaningful for Muslim families. This research employed a single-subject (AB design) experimental approach with a 4-year-old male participant. The intervention was adapted to align with Islamic values: the token economy was transformed into a